Contribution of α, β-Amyrenone to the Anti-Inflammatory and Antihypersensitivity Effects of Aleurites moluccana (L.) Willd. (19th October 2014) - Quintão, Nara Lins Meira; Rocha, Lilian W.; Silva, Gislaine Franciele; Reichert, Simone; Claudino, Vanessa D.; Lucinda-Silva, Ruth Meri; Malheiros, Angela; Souza, Márcia Maria De; Filho, Valdir Cechinel; Bellé Bresolin, Tania M.; Machado, Marina da Silva; Wagner, Theodoro Marcel; et al.
Abstract : The aim of the study was to analyze the constituents of the dichloromethane fraction obtained from A. moluccana and also to evaluate the anti-inflammatory and antinociceptive properties of α, β -amyrenone isolated from A. moluccana in mice. The dichloromethane fraction was evaluated by gas chromatography and submitted to purification. The mixture of α, β -amyrenone was isolated and then evaluated using the carrageenan-induced paw-oedema or pleurisy and CFA-induced arthritis models in mice. Five triterpenes, α, β -amyrenone, glutinol, and α, β -amyrin were isolated from dichloromethane fraction of A. moluccana leaf extract. The mixture of α, β -amyrenone, dosed orally, was able to reduce mechanical hypersensitivity and paw-oedema induced by carrageenan, interfering with neutrophil migration. Similar results were observed in the carrageenan-induced pleurisy model. Repeated administration of the compounds was also effective in reducing the mechanical sensitization and oedema developed in the arthritis model induced by CFA. In conclusion, the results demonstrate that α, β -amyrenone interferes in both acute and chronic inflammatory processes. We can infer that these effects involve, at least in part, a reduction in the neutrophil migration. Therefore, it seems reasonable to suggest that α, β -amyrenone could represent a new therapeutic tool for the management of painful and inflammatory diseases, especially those presenting a chronic profile.